2020
DOI: 10.32890/mmj.24.2020.9362
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Sustainable Entrepreneurship Model

Abstract: The most prominent feature of today’s economy is rapid change. To succeed in such an economy, countries must be able to adapt to these changes with great agility. One of the most potent tools for achieving this end is sustainable entrepreneurship. Sustainable entrepreneurs are those who undertake entrepreneurial endeavors while taking into account different aspects of social, economic and environmental sustainability. These entrepreneurs strive to keep their resources focused on sustainable development and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 93 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…From the observation results, it was obtained that many business managers were aware of the importance of innovation strategies. The most important innovation that was carried out was in the products they sell and the place of business [19]. Innovation in products is related to the content or mixture of products, and innovations are also carried out on the shape and size of the product to release new product variants [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the observation results, it was obtained that many business managers were aware of the importance of innovation strategies. The most important innovation that was carried out was in the products they sell and the place of business [19]. Innovation in products is related to the content or mixture of products, and innovations are also carried out on the shape and size of the product to release new product variants [20].…”
Section: Resultsmentioning
confidence: 99%
“…The same idea was also expressed by [18] who revealed that the capability innovation strategy based on observing changes in consumer behavior was an important reference that would maintain business sustainability. Furthermore, [19] stated that innovation with a life cycle approach and paying attention to changes in consumer tastes was an important instrument that could extend the life of the business unit developed, while [2] stated that service attribute innovation was the main tool to maintain the sustainability of the SMEs business in Surabaya.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation